2018
DOI: 10.15244/pjoes/81062
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Waste Incineration Process for Sustainable Development through Modelling, Logistics, and Simulation

Abstract: The sharp increase in the amounts and the variety of available products on the market have also caused an increase in the amounts of different packaging and other elements that come with any given product. The large amounts of communal waste stem from different anthropomorphic activities, and different aspects of human consumption cause an increased demand for effective waste disposal by incineration, separation, recycling, or organic processing. The object of modelling and simulation is the material flow of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This search for an adequate method refers to a search for effective, concentrated and divergent solutions of problems where there are complex societal and engineering factors. It also refers to changes taking place in the surroundings, as well as in technological processes [15,16,27,32,57,59,62,63], which enforce the need to search for modern methods that support the achievement of reliable FPI research. After reviewing the literature, it was concluded that the actions taken were to achieve reliable and effective fluorescent penetration inspection [10,20,21], and thus referred to the idea of sustainable development, the concept of Society 5.0 and partly the concept of Industry 4.0.…”
Section: Discussionmentioning
confidence: 99%
“…This search for an adequate method refers to a search for effective, concentrated and divergent solutions of problems where there are complex societal and engineering factors. It also refers to changes taking place in the surroundings, as well as in technological processes [15,16,27,32,57,59,62,63], which enforce the need to search for modern methods that support the achievement of reliable FPI research. After reviewing the literature, it was concluded that the actions taken were to achieve reliable and effective fluorescent penetration inspection [10,20,21], and thus referred to the idea of sustainable development, the concept of Society 5.0 and partly the concept of Industry 4.0.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the municipality is obliged to create conditions for waste separation in the municipality by a suitable system. The reason for waste sorting is saving natural resources -raw materials and energy, reducing the amount of waste in landfills, eliminating black landfills, reusing waste by recycling [11]. By sorting waste, we help the environment, thereby reducing the adverse effects of human exposure on the environment.…”
Section: Waste Economy In Municipalitiesmentioning
confidence: 99%
“…Operation of the transport system, selection of suitable means of transport, their compliance with the loading equipment have an impact on the evaluation of the transport system performance but also of the whole company [18,19].…”
Section: Introductionmentioning
confidence: 99%